On the Imperishable Reasons of Fairy-Tale Plots: The Case of “Tom Thumb” - Lassan, Eleonora (Respectus Philologicus, 2013)
This article focuses on one of the most popular plots in fairy tale culture (the plot involving the protagonist Tom Thumb), and tries to explain this popularity through the cultural archetypes that are expressed in the fairy tale. The author analyzes fairy tales of different nations involving this particular character and draws a boundary between the literary fairy tale, which is a transformation of old French fairy tales written by Charles Perrault, and different variations of literary fairy tale written by the brothers Grimm. The research shows that it is impossible to apply Propp’s method, which allows the plot to be analyzed in regard to functions and character types, to the analysis of this fairy tale. The author assumes that the fairy tale about Tom Thumb may not be regarded as magic for various reasons. On the other hand, it may be treated as an animal tale, which in Propp’s approach is assumed to have a different structure from a magic fairy tale. The researcher draws a conclusion about the different archetypes that serve as the basis for Perrault’s literary fairy tales, and the numerous variations of the plot which we may relatively denominate as “Grimms’ plot.” Furthermore, in folk tales having Grimms’ plot, Tom Thumb simultaneously performs the role of cultural hero and the role of a trickster. This is absent from Perrault’s fairy tale, because the propaganda of moral values and a distinct didactic character are traditional features of French fairy tales.
Keywords: Fairy Tale; Plot Variation; Archetypes